2022
DOI: 10.1161/jaha.121.024149
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐Related Differences in Clinical Features and In‐Hospital Outcomes of Type B Acute Aortic Dissection: A Registry Study

Abstract: Background The association between female sex and poor outcomes following surgery for type A acute aortic dissection has been reported; however, sex‐related differences in clinical features and in‐hospital outcomes of type B acute aortic dissection, including classic aortic dissection and intramural hematoma, remain to be elucidated. Methods and Results We studied 2372 patients with type B acute aortic dissection who were enrolled in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Following the onset of menopause, the incidence of hypertension among women begins to surpass that of men [ 118 ]. A history of hypertension and chronic obstructive pulmonary disease is more common among women [ 119 , 120 , 121 ]. In acute aortic dissection, women, at the time of diagnosis, are older than men and complain less frequently of an abrupt onset of pain [ 120 , 121 ].…”
Section: Sex Dimorphism and Obesity-related Cardiovascular Abnormalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the onset of menopause, the incidence of hypertension among women begins to surpass that of men [ 118 ]. A history of hypertension and chronic obstructive pulmonary disease is more common among women [ 119 , 120 , 121 ]. In acute aortic dissection, women, at the time of diagnosis, are older than men and complain less frequently of an abrupt onset of pain [ 120 , 121 ].…”
Section: Sex Dimorphism and Obesity-related Cardiovascular Abnormalitiesmentioning
confidence: 99%
“…A history of hypertension and chronic obstructive pulmonary disease is more common among women [ 119 , 120 , 121 ]. In acute aortic dissection, women, at the time of diagnosis, are older than men and complain less frequently of an abrupt onset of pain [ 120 , 121 ]. Obesity is considered an important risk factor for atrial fibrillation (AF), for which the incidence has increased significantly in recent years [ 122 ].…”
Section: Sex Dimorphism and Obesity-related Cardiovascular Abnormalitiesmentioning
confidence: 99%
“…Few studies have investigated the impact of gender in type B AAD [ 26 , 27 , 29 , 30 ]. Liang et al [ 29 ] identified, from 2009 to 2012, 9855 (women 43.6%, n = 4293) patients with type B AAD.…”
Section: Impact Of Gender In Aadmentioning
confidence: 99%
“…Takahashi et al [ 30 ] analyzed data about 2372 (695 women, 29.3%) patients with type B AAD, enrolled in the Tokyo Acute Super-Network Registry. Women were older than men and presented later at the emergency department.…”
Section: Impact Of Gender In Aadmentioning
confidence: 99%
See 1 more Smart Citation